Does Corporate Sustainability Management Moderate the Relationship between Cost Stickiness and Earnings Management?: The Case of Egypt - Hassan, Yasmine Safwat Ibrahim; Youssef, Ahmed Mahmoud Mohamed; Ahmed, Nancy Mohamed Mahmoud (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2024)
The main objective of this study is to examine the moderating role of corporate sustainability management on the relationship between cost stickiness and earnings management. in this research, a sample of 256 observations from 65 Egyptian firms listed on the Egyptian stock exchange is used for a period of five years, from 2018 to 2022. the ordinary least squares (OLS) regression is applied for four multiple regression models to test the research hypotheses. cost stickiness is measured by the model of homburg and Nasev (2008) and selling, general, and administrative expenses are used as a proxy for cost stickiness. discretionary accruals estimated from the modified jones model (1995) are used to measure earnings management, and the S&P global ESG score is used to assess a company's sustainability performance, determined by aggregating its environmental, social, and governance dimension scores. the results reveal a significant positive relationship between cost stickiness and earnings management. moreover, it is found that corporate sustainability management has a significant negative effect on cost stickiness. additionally, corporate sustainability management has a positive significant effect on earnings management. finally, the findings indicate that corporate sustainability management moderates the relationship between cost stickiness and earnings management, implying that corporate sustainability management reduces the positive impact of cost stickiness on earnings management.